Anxiety and burnout in young athletes: The mediating role of cognitive appraisal - Gomes, A. R.; Faria, S.; Vilela, C. (Scandinavian Journal of Medicine & Science in Sports, 2017)
This study tested the relationship between trait anxiety, cognitive appraisal, and athletes` burnout proposing two hypotheses: (a) there is a direct relationship between athletes` trait anxiety and cognitive appraisal and burnout; and (b) cognitive appraisal mediates the relationship between trait anxiety and burnout and this mediation occurs despite the competitive level and sport records of athletes. The study included 673 young athletes and provided measures of trait anxiety, cognitive appraisal, and burnout. Structural equation modelling indicated that cognitive appraisal mediates the relationship between trait anxiety and burnout, confirming hypothesis 2, and this model provided better fit than the direct model of hypothesis 1. However, the mediation also indicated that the direct relationship between trait anxiety and burnout should be considered. The mediating model was invariant according to competitive levels and sport records. In conclusion, cognitive appraisal is an important variable in explaining athletes` burnout.